Relationship between pre-operative serum vitamin D3 levels and post-thyroidectomy hypocalcemia: A cross sectional study - Jahana Ara, Muhammad Javaid Rashid, Muhammad Adnan Bawany, Ishfaq Ahmad Khan, Jamshed Bashir, Asma Kafeel (Drugs and Cell Therapies in Hematology, 2021)
Aim: To determine the relationship between vitamin D deficiency and the risk of developing hypocalcemia after thyroidectomy. Study design: Cross sectional study Place and duration: This study was conducted at District Head Quarter Hospital Mirpur Mathelo District Ghotki, Pakistan from March 2020 to March 2021. Methodology: A total of 100 patients were included in this study. Their vitamin D levels were assessed before surgery and the calcium levels were determined after surgery. Incidence of hypocalcemia symptoms was also assessed. Results: It was identified that the patients who were vitamin D deficient are more prone to develop hypocalcemia after thyroidectomy. A significant differentiation was observed between mean values of vitamin D in hypocalcemia and normo-calcemic group. Hypocalcemia after surgery was observed in 19 patients. Conclusion: The current study demonstrates that the level of serum vitamin D less than 35 would be considered as a potential risk for developing the hypocalcemia post thyroidectomy. Patients who have low vitamin D levels must be screened for hypocalcemia post thyroidectomy.